Pengujian Efisiensi Pasar Bentuk Setengah Kuat Secara Keputusan: Analisis Pengumuman Dividen Meningkat (Studi Empiris pada Bursa Efek Jakart Selama Krisis Moneter) - DODDY SETIAWAN; SITTI SUBEKTI (The Indonesian Journal of Accounting Research, 2013)
The purpose of this research is to examine the decisionally efficient market by analyzing the increase of dividend announcement at the Jakarta Stock Exchange during monetary crisis. The analysis involves information content, speed of market reaction and accuracy of market reaction. The test of information content is not only dividend increase but also for dividend constant and dividend decrease announcement. Samples of this research are 57 increase dividend announcements, 22 constant dividend announcement and  59 samples of decrease dividend from 1998 until 2002. We use t-test to test the hypothesis. The result shows that there are information content from dividend increase but also for dividend constant and dividend decrease announcement. The result of test speed market reaction shows that market react slowly to increase dividend announcement. There are some investors get abnormal return in continues time. The result of test accuracy market reaction shows that investors are not sophisticated toward increase dividend announcement both to increase dividend announcement of growth and non growth firms. Investors have positive reaction to increase dividend announcement of growth firms and non growth firms. Based on those results, it can be concluded that Indonesian capital market is neither yet informationally efficient market nor decisionally efficient market during monetary crisis.